2023
DOI: 10.1038/s41598-023-42990-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the roles of shape prototypicality and sexual dimorphism in ratings of the trustworthiness of faces

Kathlyne Leger,
Junzhi Dong,
Lisa M. DeBruine
et al.

Abstract: Perceptions of the trustworthiness of faces predict important social outcomes, including economic exchange and criminal sentencing decisions. However, the specific facial characteristics that drive trustworthiness perceptions remain poorly understood. Here we investigated this issue by exploring possible relationships between ratings of the trustworthiness of face images and objective assessments of two aspects of face shape that researchers have previously argued are important for perceptions of trustworthine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Sexual dimorphism of face shape was objectively measured for each of the 50 male and 50 female face images using the facefuns package (Holzleitner & DeBruine, 2021) in R (R Core Team, 2021), which implements shape analysis of images that have been delineated with standard landmarks. This method has been used in many previous studies to assess sexual dimorphism of face shape (e.g., Cai et al, 2019;Dong et al, 2023;Holzleitner et al, 2019;Leger et al, 2023;Komori et al, 2011). Shape components were first derived from Principal Component Analysis (PCA) of 132 Procrustes-aligned landmark points (see Holzleitner et al, 2019 for a diagram showing these facial landmarks) on each of the 50 male and 50 female face images.…”
Section: Sexual Dimorphism Of Face Shapementioning
confidence: 99%
See 3 more Smart Citations
“…Sexual dimorphism of face shape was objectively measured for each of the 50 male and 50 female face images using the facefuns package (Holzleitner & DeBruine, 2021) in R (R Core Team, 2021), which implements shape analysis of images that have been delineated with standard landmarks. This method has been used in many previous studies to assess sexual dimorphism of face shape (e.g., Cai et al, 2019;Dong et al, 2023;Holzleitner et al, 2019;Leger et al, 2023;Komori et al, 2011). Shape components were first derived from Principal Component Analysis (PCA) of 132 Procrustes-aligned landmark points (see Holzleitner et al, 2019 for a diagram showing these facial landmarks) on each of the 50 male and 50 female face images.…”
Section: Sexual Dimorphism Of Face Shapementioning
confidence: 99%
“…Previous work has shown that measures of face shape derived from manually placed and automatically generated image landmarks are highly correlated (Jones et al, 2021b). Scores representing sexual dimorphism of face shape were then calculated from each photograph using a vector analysis method (e.g., Cai et al, 2019;Dong et al, 2023;Holzleitner et al, 2019;Leger et al, 2023;Komori et al, 2011). This method uses the shape principal components to locate each face on a female-male continuum.…”
Section: Sexual Dimorphism Of Face Shapementioning
confidence: 99%
See 2 more Smart Citations
“…These facial features partly correspond to female-like facial shape in these populations (Ekrami et al, 2021; Kleisner et al, 2021; Mezentseva et al, 2023). Indeed, a number of studies demonstrate that perceived facial trustworthiness is related to morphological facial femininity/masculinity in Europeans, with male-specific appearance generally eliciting less trust than female-specific (Rostovtseva et al, 2023; Stirrat & Perrett, 2010; although see Leger et al, 2023 for alternative results). Another important source of facial shape variation related to trustworthy look is the resemblance of facial features to specific emotional expressions.…”
Section: Introductionmentioning
confidence: 99%